2015
DOI: 10.1159/000380871
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of Venous Thromboembolism in Ambulatory Cancer Patients in Germany: A Prospective Non-Interventional Study

Abstract: Background: Venous thromboembolism (VTE) is a serious threat for all cancer patients. This study was aimed to assess the VTE treatment of cancer patients in the ambulatory care setting. Patients and Methods: This is a prospective non-interventional study, which includes ambulatory cancer patients from office-based oncologists. A standardized case report form was used to obtain data on patient characteristics, treatment regimens, duration of treatment, and side effects. Results: Specialists from 34 centers incl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 29 publications
1
4
0
Order By: Relevance
“…However, considering the large number of participants of the DGHO annual meeting the return rate seemed to be low which was also the impression at the regional educational meetings. This observation is in line with a previous survey on VTE-practice patterns 31,38 where the return rate was only 6%. It could be that new developments in CAT-prophylaxis and treatment are not perceived as a priority issue.…”
Section: Limitationssupporting
confidence: 92%
See 1 more Smart Citation
“…However, considering the large number of participants of the DGHO annual meeting the return rate seemed to be low which was also the impression at the regional educational meetings. This observation is in line with a previous survey on VTE-practice patterns 31,38 where the return rate was only 6%. It could be that new developments in CAT-prophylaxis and treatment are not perceived as a priority issue.…”
Section: Limitationssupporting
confidence: 92%
“…Patient preferences are in the treating physician's perception much more important and rank higher than guidelines and almost all the other parameters. This gap between evidencebased recommendations and practice patterns has been noted before [31][32][33][34][35][36] and needs to be addressed in the future development of clinical guidelines.…”
Section: Scenarios In Favor Of Doacs Versus Lmwhmentioning
confidence: 98%
“…Studies investigating the efficacy of long‐term LMWH use in cancer patients found discontinuation rates varying from 33% to 58% after 3–6 months, because of complications including recurrent VTE, bleeding, or death . Furthermore, in recent studies, 11–20% of cancer patients switched from LMWH injections to oral anticoagulants within 3–6 months, possibly to avoid the discomfort of injections, or because of a lack of communication among health professionals or a deliberate physician's decision . Thus, detailed information about the burden of daily subcutaneous injections is required.…”
Section: Introductionmentioning
confidence: 99%
“…4 This finding was consistent with other smaller, retrospective studies reporting similar percentages of patients who switched to oral anticoagulants within 6 months. 5,6 These studies, however, did not distinguish between LMWH preparations.…”
Section: Introductionmentioning
confidence: 93%
“…Recent research carried out at our institution has showed that 1 out of 5 patients with cancer‐associated VTE stop LMWH injections because of side effects, mostly due to unacceptable pain at injection site 4 . This finding was consistent with other smaller, retrospective studies reporting similar percentages of patients who switched to oral anticoagulants within 6 months 5,6 . These studies, however, did not distinguish between LMWH preparations.…”
Section: Introductionmentioning
confidence: 99%